AN PERFORMANCE EFFECT OF VARIATION VOLTAGE ON POSTPAID AND PREPAID KWH ON THE NUMBER OF TURN OF KWH METER - Heru Puja Rivanda; Adi Sastra P Tarigan; Solly Aryza (Sean Institute, 2022)
Postpaid and Prepaid kWh meters are measuring tools for consumer power consumption, there is a thought that Prepaid kWh meters are more expensive than Postpaid kWh meters. This research is to compare Postpaid kWh meters and Prepaid kWh meters by using varying loads with voltage drop treatments with voltages of 230 volts, 220 volts, 198 volts, and 165 volts. So on the load of the induction motor, LHE, and the load of LHE variations and incandescent lamps with source voltages of 230 volts, 220 volts, 198 volts, and 165 volts, it can be said that the Prepaid KWH-meter has a better KWH rotation than the Postpaid KWH-meter. At various loadings on the kWh meter rotation test, the prepaid rotation speed is longer than the postpaid rotation speed with a difference of 0.53 hours or 32 minutes.